Single-cell transcriptomic analysis reveals heterogeneous features of myeloid-derived suppressor cells in newborns - Yao, Meng; Cao, Yingjiao; He, Juan; Dong, Rui; Liu, Gaoyu; Chen, Yingying; Wang, Jun; Zhou, Jie (Frontiers in Immunology, 2024)
Transitory emergence of myeloid-derived suppressor cells (MDSCs) in infants is important for the homeostasis of immune system in early life. The composition and functional heterogeneity of MDSCs in newborns remain elusive, hampering the understanding of the importance of MDSCs in neonates. In this study, we unraveled the maturation trajectory of polymorphonuclear (PMN)-MDSCs from the peripheral blood of human newborns by performing single-cell RNA sequencing. Results indicated that neonatal PMN-MDSCs differentiated from self-renewal progenitors, anti-microbial and immunosuppressive PMN-MDSCs to late PMN-MDSCs with reduced anti-microbial capacity. We also established a simple framework to distinguish these distinct stages by CD177 and CXCR2. Importantly, preterm newborns displayed reduced abundance of classical PMN-MDSCs but increased late PMN-MDSCs, consistent with their higher susceptibility of infections and inflammation. Furthermore, newborn PMN-MDSCs were distinct from those from cancer patients which displayed minimum expression of genes about anti-microbial capacity. This study indicates that the heterogeneity of PMN-MDSCs is associated with the maturity of human newborns.